2014
DOI: 10.1371/journal.pone.0088783
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expressions Depicting Compassionate and Critical Emotions: The Development and Validation of a New Emotional Face Stimulus Set

Abstract: Attachment with altruistic others requires the ability to appropriately process affiliative and kind facial cues. Yet there is no stimulus set available to investigate such processes. Here, we developed a stimulus set depicting compassionate and critical facial expressions, and validated its effectiveness using well-established visual-probe methodology. In Study 1, 62 participants rated photographs of actors displaying compassionate/kind and critical faces on strength of emotion type. This produced a new stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 66 publications
(96 reference statements)
3
36
2
Order By: Relevance
“…Others further include embarrassment, pride and shame (University of California, Davis, Set of Emotion Expressions: Tracy, Robins, & Schriber, 2009), or kindness and critical facial expressions (e.g., McEwan et al, 2014). Some databases also contain body expressions (e.g., Bochum Emotional Stimulus Set: Thoma, Soria Bauser, & Suchan, 2013;Bodily Expressive Action Stimulus Test: de Gelder & Van den Stock, 2011).…”
Section: Facial Expressions Databasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Others further include embarrassment, pride and shame (University of California, Davis, Set of Emotion Expressions: Tracy, Robins, & Schriber, 2009), or kindness and critical facial expressions (e.g., McEwan et al, 2014). Some databases also contain body expressions (e.g., Bochum Emotional Stimulus Set: Thoma, Soria Bauser, & Suchan, 2013;Bodily Expressive Action Stimulus Test: de Gelder & Van den Stock, 2011).…”
Section: Facial Expressions Databasesmentioning
confidence: 99%
“…For example, eyebrow frowning (produced by contracting the corrugator supercilii) is associated with unpleasant experiences, and raised lip corners (produced by contracting the zygomaticus major) are associated with pleasant ones (for a review, see Colombetti, 2005). The valence of facial stimuli has been assessed in a few validation studies (e.g., Adolph & Alpers, 2010;Langner et al, 2010;McEwan et al, 2014;O'Reilly et al, 2016;. In the present study, we asked participants to indicate the extent to which the expression displayed by the target was negative-positive (1 = Very negative, 7 = Very positive; e.g., Langner et al, 2010;McEwan et al, 2014;O'Reilly et al, 2016).…”
Section: Dimensions Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, as noted above, when self-critical people are invited to focus on feeling connected and being open to receiving compassion, care and concern from others, this often stimulates feelings of grief or an awareness of "how lonely one feels", and/or a sense of not deserving compassion [68]. In addition, research on emotion processing has shown that individuals who are depressed, anxious, insecurely attached or self-critical show diminished emotional processing of affiliative, kind and compassionate social cues such as positive facial expressions [69][70][71].…”
Section: Fears Blocks and Resistances To Compassionmentioning
confidence: 99%
“…McEwan et al [47] studied the effect of facial cues on self-criticism, which is an outcome behaviour of low self-compassion and acceptance. The measure for selfcriticism that was used is the Forms of Self-criticism/reassurance Scale [FSCRS; 48], which measures self-criticism vs self-reassuring of which the latter is identical to the Acceptance factor.…”
Section: Mindfulness Factor 5: Acceptancementioning
confidence: 99%